THE ANALYSIS STUDY OF RISK FACTOR, PREVENTION STRATEGIES, MANAGEMENT OF SUICIDE : A SYSTEMATIC REVIEW - Yohanes Windu Tiar Prakosa; Radian Adhiputra Antonius (PT Wahana Global Education, 2025)
Background: Protective factors, predisposing factors, and risk factors can be defined within the interdisciplinary framework that includes suicide and with particular reference to the elements that may favorably or unfavorably affect the development of suicidal behavior. Aims : This systematic review is to review the risk factor, prevention strategies and management of suicide. Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 8538 articles, whereas the results of our search on SCIENCE DIRECT brought up 40.508 articles, our search on SAGEPUB brought up 36.459 articles. The results of the search conducted for the last year of 2014 yielded a total 4881 articles for PubMed, 20.418 articles for SCIENCE DIRECT and 15.561 articles for SAGEPUB. In the end, we compiled a total of 8 papers, 5 of which came from PubMed, 2 of which came from SCIENCE DIRECT and 1 of which came from SAGEPUB. We included eight research that met the criteria. Conclusion: In summary, the therapy for managing and treating suicidal thoughts and attempts are dialectical and cognitive behavioral.